Synergistic bioremediation of marine oil spills using dual strain consortium immobilized rice husk biochar - Prithwindra Sarkar; S. Jitendra Pal (Environmental Challenges)
Bacteria capable of degrading oil spillage hydrocarbons are widely identified, yet single bacterial strains often underperform in real environments due to competition with native microorganisms, leading to decreased degradation efficiency. In this study, an eco-friendly approach was developed for removing hydrocarbons from aqueous systems by immobilizing consortium of Novosphingobium sp. MCC 3051 and Alcanivorax sp. MCC 4337 onto rice husk-derived biochar (RHB). The Hydrocarbons remediation process was systematically optimized using response surface methodology (RSM). MCC 3051 and MCC 4337 exhibited a highly hydrophobic cell surface. Genetic analysis revealed multiple metabolic pathways for breaking down both alkanes and aromatic hydrocarbons. Experimentally, MCC 3051 and MCC 4337 completely degraded short-chain Hydrocarbons (C10–C22) and achieved over 97% degradation within 7 days. These findings suggest MCC 3051 and MCC 4337 hold strong promise for remediating oil-contaminated water due to its broad degradation range and high environmental adaptability. Gas Chromatography (GC) analyses identified the degradation products, signifying a synergistic effect of bacterial metabolism and adsorption in the Hydrocarbons removal mechanism. These findings highlight the potential of immobilized MCC 3051, MCC 4337 and Consortium loaded rice husk biochar (CRHB) for efficient remediation of marine oil-contaminated environments.